All 3D Printing Shape‐Conformable Zinc Ion Hybrid Capacitors with Ultrahigh Areal Capacitance and Improved Cycle Life. Issue 27 (31st May 2022) - Liu, Yu; Zheng, Shuanghao; Ma, Jiaxin; Wang, Xiao; Zhang, Liangzhu; Das, Pratteek; Wang, Kai; Wu, Zhong‐Shuai
Abstract: Aqueous zinc ion hybrid capacitors (ZIHCs) with notable advantages like cost‐effectiveness and safety are promising new‐generation electrochemical energy storage devices (EESDs). However, unsatisfactory areal capacitance, zinc dendrites, and rigid form factor of typical aqueous ZIHCs impede their further practical applications. Herein, a protocol is developed for 3D‐printing shape‐conformable ZIHCs, including hierarchically porous microlattice cathode, metal anode stabilizer, quasisolid gel electrolyte, and plastic packages, through direct ink writing and fused deposition modeling methods. Among these components, microlattice cathodes with a high mass loading density of 22.8 mg cm −2 effectively improve the areal capacitance of ZIHCs, and the metal anode stabilizer sufficiently inhibits dendritic growth to prolong the cycle life of ZIHCs. As a result, the obtained all 3D‐printed ZIHCs deliver a high areal capacitance of 4259 mF cm −2 as well as a considerable energy density of 1514 μWh cm −2, surpassing most reported ZIHCs. The 3D‐printed metal anode stabilizer endows ZIHCs with better cycling stability with almost no capacitance loss after 10 000 cycles. Impressively, the ZIHCs can easily be manufactured into shape‐conformable devices encapsulated by 3D‐printed polylactic acid package, demonstrating their viability. Therefore, this all 3D‐printing strategy provides a general and innovative methodology for constructing customized EESDs. Abstract : A new strategy for the fabrication of all 3D‐printing shape‐conformable zinc ion hybrid capacitors is demonstrated, including hierarchically porous microlattice cathode, metal anode stabilizer, quasisolid gel electrolyte, and plastic packages by direct ink writing and fused deposition modeling methods. The resultant hybrid capacitors exhibit ultrahigh areal capacitance and excellent cycling stability.